A NEW CHIRAL SYNTHETIC ROUTE TO (+)-ISOCARBACYCLIN - PARK, H; LEE, YS; SHIM, SC (KOREAN CHEMICAL SOC, 1993)
A synthetic route to (+)-isocarbacyclin starting from (-)-tricyclo[3.3.0.0(2,8)]octan-3-one 6 is described. The key intermediate 4 has been synthesized from 6 by a sequential introduction of methoxycarbonyl group at C-12 and the oxygen functionality at C-9alpha (PG numbering) for the construction of alpha- and omega-side chain, and then converted to isocarbacyclin methyl ester 2.